Liquid organic fertilizer from seaweed (Sargassum sp.)and fish waste hydrolysate - Jamal Basmal (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2010)
The combination of seaweed Sargassum sp. and fish waste hydrolysate can be used as anorganic fertilizer, both in liquid or solid forms. The organic fertilizer has a complete macro andmicro nutrients. It contains growth hormone factor such as auxin, cytokinine (zeatin and kinetin)and giberelin. The function of growth hormone factor in plants is to enhance the roots, stems, andleaves expansion, as well as to increase fruit production. To produce liquid organic fertilizer,seaweed has to be hydrolyzed in alkaline condition, meanwhile solid waste of fish has to behydrolyzed in acid condition. The liquid organic fertilizer had protein value of 0.08% or equal to0.012% N, 0.13% P, 1.22% K, 0.06% Ca, 0.17% Mg, 55.04% Fe, 122.75 ppm Mn, 1.95 ppm Cu,24.59 ppm Zn, 13 ppm B, and 18% alginic acid. It had auxin (IAA) of 91.48 ppm, cytokinine of84.71 ppm kinetin and of 70.27 ppm zeatin and giberellin (GA3) of 107.72 ppm.